The Body as the Affective Materiality of Ageing in a Future City - Suopajärvi Tiina (Berghan Journals, 2025)
In this article, I discuss the way that the body becomes the crucial socio-material element of ageing in a future city when it is imagined in participatory workshops involving seniors, city officials and researchers and when this joint learning process is analysed through the lens of affect theory. The analysis shows how the materiality of bodies that move between places and with other human and nonhuman bodies adds to the anthropological understanding of ageing as an experienced and cultural phenomenon, as well as the understanding of ageing as a human–nonhuman assemblage. Furthermore, analysing participatory design processes through the lens of affects generates knowledge on how emotions participate in the making of boundaries that are essential when designing not only to cater to senior city dwellers, but also to anyone.